Polymer of Intrinsic Microporosity (PIM‐7) Coating Affects Triphasic Palladium Electrocatalysis. Issue 16 (7th November 2018) - Mahajan, Ankita; Bhattacharya, Swapan K.; Rochat, Sébastien; Burrows, Andrew D.; Fletcher, Philip J.; Rong, Yuanyang; Dalton, Alan B.; McKeown, Neil B.; Marken, Frank
Abstract: A film of the polymer of intrinsic microporosity PIM‐7 is coated onto a glassy carbon electrode and the resulting effects on electron transfer reactions are studied for three different types of processes: (i) aqueous solution based, (ii) solid state surface immobilised, and (iii) electrocatalytic processes on electrodeposited palladium. The effects on reactivity for hydroquinone oxidation in aqueous phosphate buffer are shown to be linked to microporosity causing a slightly lower rate of mass transport without detrimental effects on electron transfer and reaction kinetics. Next, water‐insoluble microcrystalline anthraquinone is immobilised directly into the PIM‐7 film and shown to give a chemically reversible reduction process, which is enhanced in the presence of PIM‐7, when compared to the case of anthraquinone immobilised directly onto bare glassy carbon. Electrodeposition of a film of nano‐palladium is demonstrated to give catalytically active electrodes for the reduction/oxidation of protons/hydrogen, the reduction of oxygen, and for the oxidation of formic acid and methanol. With the PIM‐7 film applied onto palladium, a mechanical stabilisation effect occurs. In addition, both the hydrogen insertion and the hydrogen evolution reactions as well as formic acid oxidation are enhanced. Effects are discussed in terms of PIM‐7 beneficially affecting the interfacial reaction under triphasic conditions. The microporous polymer acts as an interfacial "gas management" layer. Abstract : A microporous polymer film of PIM‐7 is coated onto a glassy carbon electrode, the effects on (i) aqueous solution based, (ii) solid state surface immobilised, and (iii) electrocatalytic processes on electrodeposited palladium are investigated. Triphasic electrochemical processes involving gas evolution are beneficially affected by the presence of microporous PIM‐7 polymer coated over the electrode surface.